Titanium surface with nanospikes tunes macrophage polarization to produce inhibitory factors for osteoclastogenesis through nanotopographic cues. (1st January 2022) - Kartikasari, Nadia; Yamada, Masahiro; Watanabe, Jun; Tiskratok, Watcharaphol; He, Xindie; Kamano, Yuya; Egusa, Hiroshi
Abstract: Definitive prevention of inflammatory osteolysis around peri-implant bone tissue remains unestablished. M1 macrophages play a key role in the host defense against inflammatory osteolysis, and their polarization depends on cell shape. Macrophage polarization is controlled by environmental stimuli, particularly physicochemical cues and hence titanium nanosurface might tune macrophage polarization and function. This study determined whether titanium nanosurfaces with anisotropically patterned nanospikes regulates macrophage polarization for inhibiting osteoclast differentiation of osteoclast precursors. Alkaline-etching treatment with different protocols created two types of titanium nanosurfaces that had anisotropically patterned nanospikes with high or low distribution density, together with superhydrophilicity and the presence of hydroxyl groups. J774A.1 cells (mouse macrophage-like cell line), cultured on both titanium nanosurfaces, exhibited truly circulated shapes and highly expressed M1, but less M2, markers, without loss of viability. M1-like polarization of macrophages on both titanium nanosurfaces was independent of protein-mediated ligand stimulation or titanium surface hydrophilic or chemical status. In contrast, other smooth or micro-roughened titanium surfaces with little or no nanospikes did not activate macrophages under any culture conditions. Macrophage culture supernatants on both titanium nanosurfaces inhibited osteoclast differentiation of RAW264.7 cells (mouse osteoclast precursor cell line), even when co-incubated with osteoclast differentiation factors. The inhibitory effects on osteoclast differentiation tended to be higher in macrophages cultured on titanium nanosurfaces with denser nanospikes. These results showed that titanium nanosurfaces with anisotropically patterned nanospikes tune macrophage polarization for inhibiting osteoclast differentiation of osteoclast precursors, with nanotopographic cues rather than other physicochemical properties. Statement of significance: Peri-implant inflammatory osteolysis is one of the serious issues for dental and orthopedic implants. Macrophage polarization and function are key for prevention of peri-implant inflammatory osteolysis. Macrophage polarization can be regulated by the biomaterial's surface physicochemical properties such as hydrophilicity or topography. However, there was no titanium surface modification to prevent inflammatory osteolysis through immunomodulation. The present study showed for the first time that the titanium nanosurfaces with anisotropically patterned nanospikes, created by the simple alkali-etching treatment polarized macrophages into M1-like type producing the inhibitory factor on osteoclast differentiation. This phenomenon attributed to nanotopographic cues, but not hydrophilicity on the titanium nanosurfaces. This nanotechnology might pave the way to develop the smart implant surface preventing peri-implant inflammatory osteolysis through immunomodulation. Graphical abstract: Image, graphical abstract